2000
DOI: 10.1034/j.1399-3054.2000.1100310.x
|View full text |Cite
|
Sign up to set email alerts
|

Lead disturbs microtubule organization in the root meristem of Zea mays

Abstract: effects of lead on microtubules in the root meristem. LeadLead is an environmental pollutant that interferes with plant growth. Unfortunately, the mechanisms of lead toxicity in treatment perturbed the alignment of microtubules in a concentration-dependent manner beginning at 10 mM. Microtubules of plants are still poorly understood. In this study, we have investigated both the deposition sites and sources of cellular different regions of the root meristem and in different stages of the cell cycle showed diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
56
1
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 141 publications
(65 citation statements)
references
References 28 publications
7
56
1
1
Order By: Relevance
“…Shoot 109 Cd(II) contents did not differ between the pretreated and control groups of plants and were less than 8% of those in the root (data not shown). This result is consistent with previous findings that reported that only a small portion of heavy metals in the root is translocated to the shoot (36,37). In the root, 109 Cd(II) content of Cd(II)-pretreated wheat was 75% that in control without pretreatment (Fig.…”
Section: Cd(ii)-pretreated Wheat Seedlings Accumulate Less Cd(ii) In supporting
confidence: 83%
“…Shoot 109 Cd(II) contents did not differ between the pretreated and control groups of plants and were less than 8% of those in the root (data not shown). This result is consistent with previous findings that reported that only a small portion of heavy metals in the root is translocated to the shoot (36,37). In the root, 109 Cd(II) content of Cd(II)-pretreated wheat was 75% that in control without pretreatment (Fig.…”
Section: Cd(ii)-pretreated Wheat Seedlings Accumulate Less Cd(ii) In supporting
confidence: 83%
“…Not only disturbs the growth of plant and causes sharp decrease in crop productivity (Hall 2002), Pb accumulation in the human body damages the brain, kidney, the reproductive and nervous systems (Body et al 1991, Rensing et al 1998, Eun et al 2000.…”
Section: ⎯⎯⎯⎯mentioning
confidence: 99%
“…Thus, these results indicate that the early prothallial growth of Athyrium gametophytes can tolerate lead toxicity. In general, however, the target of lead toxicity in higher plants is the root (Wierzbicka 1999;Eun et al 2000). Therefore, we further examined the effect of Pb 2+ on rhizoid development, since the function of rhizoids seems to be analogous to that of roots in higher plants (Racusen 2002).…”
Section: Effect Of Heavy Metal Ions On Spore Germinationmentioning
confidence: 99%